English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

(3+h)^2=(3+h)(3+h)
=9+6h+h^2
The equation becomes ((9+6h+h^2)-9)/h
=(6h+h^2)/h
=h(6+h)/h
=6+h
=6+0 when h->0
=6

2007-10-23 17:13:04 · answer #1 · answered by mlam18 6 · 0 0

Hello,

Rewrite as lim h--> 0 [(6 + 2h -9)/h] = (-3 + 2h)/h now write as two fractions lim h--> 0 -3/h + 2h/h so -3/h + 2 as h---> 0 we have 2 as the limit.

Hope This Helps!!

2007-10-23 21:43:29 · answer #2 · answered by CipherMan 5 · 0 0

fedest.com, questions and answers